2016
DOI: 10.1038/ncb3295
|View full text |Cite
|
Sign up to set email alerts
|

The LINK-A lncRNA activates normoxic HIF1α signalling in triple-negative breast cancer

Abstract: Although long noncoding RNAs (lncRNAs) predominately reside in nuclear and exert their functions in many biological processes, their potential involvement in cytoplasmic signal transduction remains unexplored. Here, we identified a cytoplasmic lncRNA, Long-Intergenic Noncoding RNA for Kinase Activation (LINK-A), which mediates HB-EGF triggered, EGFR:GPNMB heterodimer-dependent HIF1α phosphorylation at Tyr565 and Ser797 by BRK and LRRK2 respectively. These events cause HIF1α stabilization, HIF1α-p300 interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
446
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 465 publications
(460 citation statements)
references
References 64 publications
(62 reference statements)
9
446
1
4
Order By: Relevance
“…In this study, GPNMB was associated with an HB-EGF-stimulated EGFR:GPNMB heterodimer complex [45]. Upon HB-EGF stimulation, EGFR phosphorylated the tyrosine residue in GPNMB’s hemITAM motif, leading to heterodimer formation and interaction with LINK-A (long intergenic non-coding RNA for kinase activation), a cytoplasmic long non-coding RNA (lncRNA).…”
Section: Gpnmb In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, GPNMB was associated with an HB-EGF-stimulated EGFR:GPNMB heterodimer complex [45]. Upon HB-EGF stimulation, EGFR phosphorylated the tyrosine residue in GPNMB’s hemITAM motif, leading to heterodimer formation and interaction with LINK-A (long intergenic non-coding RNA for kinase activation), a cytoplasmic long non-coding RNA (lncRNA).…”
Section: Gpnmb In Cancermentioning
confidence: 99%
“…Upon HB-EGF stimulation, EGFR phosphorylated the tyrosine residue in GPNMB’s hemITAM motif, leading to heterodimer formation and interaction with LINK-A (long intergenic non-coding RNA for kinase activation), a cytoplasmic long non-coding RNA (lncRNA). This complex formation then activated BRK (Breast tumor kinase), which mediated phosphorylation of hypoxia-inducible factor 1-alpha (HIF1α), allowing for its stabilization and upregulation of target genes, thereby promoting glycolysis reprogramming and tumorigenesis [45]. …”
Section: Gpnmb In Cancermentioning
confidence: 99%
“…269.7 nM of Lnc-BM reaches 50% maximal binding with JAK2, but not other lncRNAs that are highly expressed in breast cancer, including H19 (29) and LINK-A (ref. 26 and Figure 9E). Prediction of the secondary structure of Lnc-BM suggests that the 60-mer RNA fragment (nt 961-1,020) of Lnc-BM forms 3 stemloop structures (Supplemental Figure 8G).…”
Section: Lnc-bm Mediates Jak2/stat3 Signaling That Is Triggered By Osmmentioning
confidence: 99%
“…Using high-throughput technologies, thousands of lncRNAs have recently been identified, and a large number of studies have demonstrated that dysregulated lncRNAs are closely related to human cancers [7], such as HCC [8], lung cancer [9], breast cancer [10], and colorectal cancer [7]. The expression levels of certain lncRNAs are associated with the recurrence [11], metastasis [12], and prognosis of cancers.…”
Section: Introductionmentioning
confidence: 99%